Antivirals for COVID-19 - Srinivas, Pavithra; Sacha, Gretchen L.; Koval, Christine (Cleveland Clinic Journal of Medicine, 2020)
Drugs targeting RNA respiratory viruses have resulted in few effective therapies, highlighting challenges for antivirals to treat COVID-19. Several antivirals are being investigated for symptomatic COVID-19 but no definitive data support their clinical use. Remdesivir appears to result in favorable outcomes with shortened time to recovery and a modest decrease in mortality for hospitalized patients in compassionate use series and some randomized controlled trials. Currently, remdesivir is available only from the US government via an emergency use authorization process. A randomized controlled trial of lopinavir/ritonavir demonstrated no apparent clinical or virologic benefit and drug-drug interactions and side effects further limit its utility. Antivirals to treat influenza (oseltamivir) have limited activity against SARS-CoV-2, but favipiravir and umifenovir, two influenza antivirals available internationally, may have distinct viral targets and require further investigation. Antivirals with evidence of clinical activity must be studied as treatment and prophylaxis for those at high risk for severe COVID-19.